Infected bodies, foreign bodies: literature and life in Fruta podrida by Lina Meruane - Juan Recchia Paez (Estudios de Teoría Literaria, 2018)
In this article we will explore the novel Fruta podrida (2007) by Lina Meruane with the aim of dismembering the particular relationship between social discourses (determined by what we call "medical-mercantile knowledge"), and other ways of subjectivities ("strange" and "infected") in the dispute for the assignment of meaning to the concept of "life." In contrast to the theoretical critique of Michel Foucault (2001), Judith Butler (2006), Roberto Esposito (2016), Jean Luc Nancy (2003) and Jaques Derrida (1975), the novel of Meruane explains how the notion of body problematizes the link between literature and life. And, at the same time, it shows the processes of resistance of subjectivities in front of the systemic structures imposed by certain spaces of knowledge.